CARE PRACTICES FOR PEOPLE WITH HUNTINGTON’S DISEASE FROM THE PERSPECTIVE OF FAMILY CAREGIVERS - Pleutim, Nathalia Ivulic; Arruda, Bianca Cristina Ciccone Giacon; Arruda, Guilherme Oliveira de; Palasson, Rosilene Rocha; Marcon, Sonia Silva; Teston, Elen Ferraz (Cogitare Enfermagem, 2024)
Objective: to learn about care practices for people with Huntington’s disease. Method: a qualitative study using the Patient- and Family-Centered Care framework, carried out with 20 family caregivers of people with Huntington’s disease. Data was collected through semi-structured interviews, in February and March 2022, via Google Meet, and after being transcribed in full, it was submitted to Content Analysis. Results: The practice of caring for people with Huntington’s requires adapting to the environment, readjusting the routine, and improvising aids. The difficulty in obtaining a diagnosis makes family members proactive in their search for knowledge to improve care conditions. Conclusion: although this is a rare disease, the care actions mentioned are like those carried out for people with other chronic diseases. However, recognizing the care practices carried out by family members can help nurses plan their care.